Correlation between serologic parameters and disease activity of IgG4-related disease: Differences between patients with normal and elevated serum IgG4 concentrations - Kwon, Oh Chan; Park, Min-Chan; Kim, Yong-Gil (Frontiers in Immunology, 2022)
Objective: We aimed to identify serologic parameters that correlate with the disease activity of IgG4-related disease (IgG4-RD) in patients with normal and elevated serum IgG4 concentrations, respectively. Methods: This retrospective cohort study included 148 patients with IgG4-RD. Patients were categorized into normal (≤201 mg/dL) and elevated (>201 mg/dL) serum IgG4 concentration groups. Disease activity was assessed using the IgG4-RD responder index (RI). The correlations between IgG4-RD RI and serologic parameters (erythrocyte sedimentation rate [ESR], C-reactive protein, C3, C4, IgG4 concentration, IgG concentration, and IgG4/IgG ratio) were evaluated in each group, using Spearman’s correlation coefficient. Results: Of the 148 patients with IgG4-RD, 38 (25.7%) and 110 (74.3%) patients were categorized into the normal and elevated serum IgG4 concentration groups, respectively. In the normal serum IgG4 concentration group, IgG concentration was the only serologic parameter that showed a significant correlation with IgG4-RD RI (rho=0.411, p=0.013). However, in the elevated serum IgG4 concentration group, ESR (rho=0.196, p=0.041), C3 (rho=-0.432, p<0.001), C4 (rho=-0.363, p=0.001), IgG4 concentration (rho=0.423, p<0.001), IgG concentration (rho=0.224, p=0.020), and IgG4/IgG ratio (rho=0.328, p=0.001) correlated with IgG4-RD RI. The combination of C3 and IgG4 concentration (rho=0.509, p<0.001) had the strongest correlation with IgG4-RD RI in this group. Conclusion: Among the serologic parameters tested, IgG concentration was the only parameter that correlated with IgG4-RD RI in patients with normal serum IgG4 concentrations, whereas multiple parameters correlated with IgG4-RD RI in those with elevated serum IgG4 concentrations. The combination of C3 and IgG4 concentration had the strongest correlation coefficient in the latter group.